Valorization of food waste into functional ingredients supports a sustainable strategy for the food industry - Md. Suhel Mia; Md. Monir Ahmed; Wahidu Zzaman (Discover Food)
Abstract Food waste contains valuable compounds such as polyphenols, dietary fibers, and proteins that can be recovered and utilized in functional food systems. However, existing literature often lacks an integrated view that connects specific food waste types with suitable extraction technologies and their potential applications in functional food systems. This review explores the sources of food waste generation and their valorization into food products by analyzing recent published works. It highlights key findings by identifying major compounds such as polyphenols, dietary fibers, and proteins derived from food waste, along with their recovery methods and incorporation into value-added food products. It also highlights the benefits and challenges of this pathway, offering new insights into sustainable waste utilization strategies and contributing to current research on circular bioeconomy practices. Concluding that the valorization of food waste is a promising strategy for addressing global food waste issues and achieving sustainable waste management.